Luminescent material of copper-doped bismuth-based perovskite and preparation method thereof

By doping copper ions in bismuth-based perovskites, the energy band structure of the material is optimized, and the instability and toxicity of traditional perovskite materials in different environments is solved, and the efficient photoelectric performance and long-term stability of the material are achieved. .

CN119463875AActive Publication Date: 2025-02-18CHONGQING INST OF NEW ENE STOR MATER & EQUIP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411543604.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-18
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Traditional halogenated perovskite materials are unstable in high temperature, light, polar solvents, humid environments and oxygen. Lead-based perovskites are limited in application due to toxicity problems. The chemical stability of tin-based and germanium-based perovskites is poor, affecting the photoelectric performance. and long-term stability.

Method used

A copper-doped bismuth-based perovskite luminescent material is used to adjust the lattice structure of Cs3Bi2Br9 perovskite, and copper ions are introduced to optimize the energy band structure and improve the stability and photoelectric properties of the material.

Benefits of technology

Through copper doping, the stability and photoelectric properties of the material are significantly improved, the luminescent quantum yield is improved, and the cost is low, making it suitable for use in the field of optoelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463875A_ABST
    Figure CN119463875A_ABST
Patent Text Reader

Abstract

The invention relates to the field of luminescent materials, and particularly discloses a luminescent material of copper-doped bismuth-based perovskite. The structural formula is Cs3Bi2Br9: Cu < 2 + >. The raw materials comprise a precursor solution, a CuBr2 ethanol solution and an oleic acid-ethanol solution, the precursor solution comprises the raw materials of CsBr, BiBr3, dimethyl sulfoxide and n-octylamine, and the ratio of CsBr to BiBr3 to dimethyl sulfoxide to n-octylamine is (0.3-0.5 mmol): (0.2-3.3 mmol): (5.8-6.3 ml): (60-70 [mu] l); the ratio of the amount of substance of CsBr to the amount of substance of BiBr3 is 1.3 to 1.6; the raw materials of the CuBr2 ethanol solution comprise absolute ethyl alcohol and CuBr2, and the ratio of the absolute ethyl alcohol to the CuBr2 is (2.3-2.6) ml: (0.05-0.06) mmol; the oleic acid-ethanol solution is prepared from the following raw materials in parts by volume: 4.3 to 5 parts of absolute ethyl alcohol and 0.35 to 0.6 part of oleic acid; the ratio of the volume sum of the CuBr2 ethanol solution and the oleic acid-ethanol solution to the volume of the precursor solution is 10: 1. According to the copper-doped bismuth-based perovskite luminescent material in the scheme, the photoelectric property and long-term stability of the material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of luminescent materials, and in particular to a luminescent material of a copper-doped bismuth-based perovskite and a preparation method thereof. Background Art

[0002] Perovskite materials are a class of ceramic oxides with a special crystal structure, with the chemical formula ABX 3 It is stated that perovskite has shown great potential in the field of optoelectronic devices with its unique crystal structure and excellent optoelectronic properties. However, the instability of traditional halide perovskites, especially in the presence of high temperature, light, polar solvents, humid environment and oxygen, has severely limited its widespread application. In addition, lead halide perovskites (LHPs) have made significant progress in the photovoltaic field due to their strong optical absorption, low exciton binding energy, long diffusion length, high carrier mobility and simple preparation. However, the lead element they contain is highly toxic and does not meet the requirements of environmental protection regulations, which hinders their promotion in consumer electronics and other fields. Therefore, lead-free perovskite materials are needed. However, both tin-based and germanium-based perovskites have problems such as poor chemical stability and easy oxidation, which affect the optoelectronic properties and long-term stability of the materials.

[0003] At present, there is a perovskite / polymer composite luminescent material and its preparation method disclosed in application number CN201510245596.6, which consists of two parts, perovskite and polymer, and the perovskite particles are embedded in the molecular gap of the polymer. The mass ratio of perovskite particles to polymer is: perovskite particles: polymer = 1: (1-50); wherein the structural formula of perovskite is R 1 NH 3 AB 3 or (R 2 NH 3 ) 2 AB 4 , where A and B form a coordinated octahedral structure, R 1 NH 3 or R 2 NH 3 Filling in the coordination octahedron gap formed by A and B, R 1 is methyl, R 2It is a long-chain organic molecule group, A is any one of metal Ge, Sn, Pb, Cu, Mn, Sb or Bi, and B is any one of Cl, Br or I; the polymer is any one of polyvinylidene fluoride (PVDF), polyvinyl acetate (PVAc), cellulose acetate (CA), and polysulfone (PSF). However, the above materials are composite materials of polymers and lead-based perovskites. Lead perovskites are highly toxic and unsatisfactory in terms of environmental protection. Secondly, there are interface problems between lead perovskites and polymers, which is not conducive to electron transfer and thus affects the photoelectric conversion efficiency. In addition, the polymer is prone to aging, resulting in poor long-term stability of the material. Summary of the invention

[0004] The present invention aims to provide a copper-doped bismuth-based perovskite luminescent material and a preparation method thereof, so as to improve the photoelectric performance and long-term stability of the material.

[0005] To achieve the above-mentioned purpose, the present invention adopts the following technical solution: a copper-doped bismuth-based perovskite luminescent material, the structural formula of which is Cs3Bi2Br9:Cu2+.

[0006] Further, the raw materials include a precursor solution, a CuBr2 ethanol solution and an oleic acid-ethanol solution, and the raw materials of the precursor solution include CsBr, BiBr 3 , dimethyl sulfoxide and n-octylamine, and CsBr:BiBr 3 :Dimethyl sulfoxide:n-octylamine is 0.3~0.5mmol:0.2~3.3mmol:5.8~6.3ml:60~70μl;CsBr / BiBr 3 The amount of substance ratio is 1.3 to 1.6;

[0007] The raw materials of CuBr2 ethanol solution include anhydrous ethanol and CuBr2, anhydrous ethanol: CuBr2 is 2.3-2.6ml: 0.05-0.06mmol;

[0008] The oleic acid-ethanol solution comprises the following raw materials in parts by volume: 4.3-5 parts of anhydrous ethanol and 0.35-0.6 parts of oleic acid;

[0009] The ratio of the sum of the volumes of the CuBr2 ethanol solution and the oleic acid-ethanol solution to the volume of the precursor solution is 10:1.

[0010] The beneficial effects of this program are:

[0011] The copper doping ratio in this scheme refers to Cu 2+ The doping ratio of the substance is Cu / (Cu+Bi) mol%. After doping with Cu2+, Cu2+ will enter the Cs3Bi2Br9 perovskite lattice and cause the lattice to shrink, thereby reducing the Cs 3 Bi 2X 9 The gap value of perovskite optimizes the energy band structure, making the material more stable. At the same time, new luminescence centers are introduced or the electron transition process is improved, reducing non-radiative transitions, and significantly improving the luminescence quantum yield of the material.

[0012] Compared with other metal doping, copper doping is low-cost. As a common metal element, copper has low cost and abundant reserves. The photoelectric performance is enhanced, and copper ions can occupy a specific position in the perovskite structure to form a stable structure, while changing the energy band structure of the perovskite, enhancing its light absorption ability and charge transfer efficiency, thereby improving the photoelectric conversion efficiency. The stability is improved, and copper ions can also form chemical bonds with other elements in the perovskite, further enhancing the stability of the perovskite.

[0013] A method for preparing a copper-doped bismuth-based perovskite luminescent material comprises the following steps:

[0014] Step 1, CsBr, BiBr3, dimethyl sulfoxide, and n-octylamine are mixed until the particles in the solution are completely dissolved to obtain a precursor solution;

[0015] Step 2, mixing CuBr2 with anhydrous ethanol and stirring until the particles in the solution are completely dissolved to obtain a CuBr2 ethanol solution;

[0016] Step 3, mixing anhydrous ethanol and oleic acid to obtain an oleic acid-ethanol solution;

[0017] Step 4, mixing the CuBr2 ethanol solution and the oleic acid-ethanol solution at 50-90° C., and then injecting the precursor solution to obtain a quantum dot solution;

[0018] Step 5, separating the upper clear layer of the quantum dot solution to obtain a colloidal solution.

[0019] The luminescent material in this scheme exists in the form of a particle suspension in the colloidal solution, that is, the luminescent particles and the liquid together form a liquid luminescent material. In this scheme, a high-concentration CuBr2 ethanol solution is first prepared, and then the concentration of CuBr2 can be more conveniently adjusted by adding oleic acid-ethanol solution, thereby improving the purity of the prepared material.

[0020] Further, the stirring temperature in step 1 is room temperature.

[0021] The beneficial effect of this scheme is that the stirring temperature of this scheme can better promote the dissolution of CsBr and BiBr3, thereby preparing the precursor solution in a shorter time.

[0022] Furthermore, at least one of step 1 and step 2 is subjected to stirring or ultrasonic dissolution during mixing.

[0023] The beneficial effects of this solution are: stirring and ultrasonic dissolution can promote the dissolution of particles more quickly, further improving the preparation efficiency.

[0024] Furthermore, in step 4, mixing is performed at 70-85°C.

[0025] The beneficial effect of this scheme is that the Cs3Bi2Br9:Cu2+ perovskite quantum dot colloid prepared in this scheme has the best fluorescence performance.

[0026] Furthermore, the stirring time of step 4 is 5 to 10 minutes.

[0027] The beneficial effect of this scheme is: this scheme can ensure that Cu2+ has enough time to enter the Cs3Bi2Br9 lattice, and the fluorescent performance of the luminescent material obtained is the best.

[0028] Furthermore, step 5 is performed by centrifugation, and the centrifugal speed is 5000-8000 rpm, and the centrifugal time is 5-10 min.

[0029] The beneficial effect of this scheme is that the luminescent material obtained by this scheme is suspended in the colloidal solution in the form of small particles, and the particle sizes of the small particles are different. The centrifugal separation of this scheme can separate particles with relatively larger particle sizes, thereby making the particle sizes of the particles in the remaining liquid material more uniform, so that when used in the form of a solution, the luminescent effect of the material is more uniform.

[0030] Furthermore, in step 5, the liquid material is separated again by centrifugation, and the centrifugal speed is greater than or equal to 10000 rpm, the centrifugal time is greater than or equal to 10 min, and the precipitate is separated to obtain a solid material.

[0031] The beneficial effect of this solution is that this solution can further separate the luminescent particles therein, and the luminescent material exists in a solid state at this time, and can be used in places where liquid is inconvenient to use. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The microstructure diagram of the luminescent material obtained in Examples 2 to 7 of the present invention;

[0033] Figure 2 is the fluorescence emission spectrum of the colloidal solution;

[0034] Figure 3 is the XRD pattern of the material;

[0035] Figure 4 is the fluorescence quantum yield diagram of the material;

[0036] Figure 5 This is a graph showing the relationship between the residual relative fluorescence intensity of the material and the change in the added water content;

[0037] Figure 6 This is a graph showing the relationship between the residual relative fluorescence intensity of the colloidal solution after adding 50% water content and the change in time. DETAILED DESCRIPTION

[0038] The following is further described in detail through specific implementation methods:

[0039] Example

[0040] A copper-doped bismuth-based perovskite luminescent material, such as Figure 1 As shown, the structural formula is Cs3Bi2Br9:Cu2+. The raw materials include precursor solution, CuBr2 ethanol solution and oleic acid-ethanol solution.

[0041] The raw materials of the precursor solution include CsBr, BiBr3, dimethyl sulfoxide and n-octylamine, and CsBr:BiBr 3 :Dimethyl sulfoxide:n-octylamine is 0.3~0.5mmol:0.2~3.3mmol:5.8~6.3ml:60~70μl;CsBr / BiBr 3 The amount of substance ratio is 1.3 to 1.6;

[0042] The raw materials of CuBr2 ethanol solution include anhydrous ethanol and CuBr2, anhydrous ethanol: CuBr2 is 2.3-2.6ml: 0.05-0.06mmol;

[0043] The oleic acid-ethanol solution comprises the following raw materials in parts by volume: 4.3-5 parts of anhydrous ethanol and 0.35-0.6 parts of oleic acid;

[0044] The ratio of the sum of the volumes of the CuBr2 ethanol solution and the oleic acid-ethanol solution to the volume of the precursor solution is 10:1.

[0045] The present invention also discloses a method for preparing a light-emitting material of a copper-doped bismuth-based perovskite. The specific ratio of the raw materials used in the preparation method is as follows:

[0046] The raw materials of the precursor solution include 0.4mmolCsBr, 0.268mmolBiBr3, 6ml dimethyl sulfoxide and 66μl n-octylamine;

[0047] The raw materials of CuBr2 ethanol solution include 5 ml of anhydrous ethanol and 0.112 mmol of CuBr2;

[0048] The raw materials of oleic acid-ethanol solution include 4.889 ml of anhydrous ethanol and 0.5 ml of oleic acid;

[0049] The ratio of the sum of the volumes of the CuBr2 ethanol solution and the oleic acid-ethanol solution to the volume of the precursor solution is 10:1.

[0050] A method for preparing a copper-doped bismuth-based perovskite luminescent material comprises the following steps:

[0051] Step 1, CsBr, BiBr3, dimethyl sulfoxide, and n-octylamine are mixed, and stirred at room temperature until the particles in the solution are completely dissolved to obtain a precursor solution;

[0052] Step 2, mixing CuBr2 with anhydrous ethanol and stirring until the particles in the solution are completely dissolved to obtain a CuBr2 ethanol solution;

[0053] Step 3, mixing anhydrous ethanol and oleic acid in a volume ratio of 4.889:0.5 to obtain an oleic acid-ethanol solution;

[0054] Step 4, mixing the CuBr2 ethanol solution and the oleic acid-ethanol solution and stirring for 10 minutes, and injecting the precursor solution at 85° C. while stirring to obtain a quantum dot solution;

[0055] Step 5, centrifuging the quantum dot solution at a centrifugal speed of 5000-8000 rpm for 5-10 min, separating the supernatant to obtain a liquid material; in actual implementation, the precipitate in the quantum dot solution can also be filtered out to obtain a colloidal solution, and then the colloidal solution is centrifuged at 5000-8000 rpm, at which time the luminescent particles with relatively large particle size in the colloidal solution can be separated;

[0056] When it is necessary to use solid luminescent particles directly, the liquid material is finally separated again by centrifugation, and the centrifugal speed is greater than or equal to 10000rpm, the centrifugal time is greater than or equal to 10min, and the precipitate is separated, and the precipitate is the solid material.

[0057] In actual implementation, the stirring in step 1 and step 2 may also be carried out by ultrasonic dissolution to increase the dissolution rate.

[0058] The present invention discloses embodiments 1 to 7, and the Cu2+ theoretical doping ratios of embodiments 1 to 7 are different, wherein the doping ratio of embodiment 1 is 0, i.e., Undoped, as shown in the following Table 1:

[0059]

[0060] The luminescent particles obtained in step 5 were washed and dissolved in an equal amount of anhydrous ethanol to obtain a sample solution that meets the ICP test. Then, an inductively coupled plasma optical emission spectrometer (ICP-OES) was used to quantitatively analyze the element concentration in the sample solution using a standard curve to obtain the contents of Cu and Bi in Examples 1 to 7 and the actual doping ratio of Cu2+ as follows:

[0061] As shown in Table 2:

[0062]

[0063]

[0064] Since the sample had been processed by centrifugation, washing and re-dissolving before analysis, and the above analysis confirmed that the luminescent material prepared by the preparation method contained Cu2+ ions, it is believed that the Cu2+ ions have undergone partial ion exchange with the Cs3Bi2Br9 perovskite quantum dots to produce the Cs3Bi2Br9:Cu2+ luminescent material.

[0065] The following tests were performed on the liquid materials prepared in Examples 1 to 7:

[0066] 1. Fluorescence emission spectrum (PL) test: The colloidal solution prepared in step 5 was tested using a FLS1000 steady-state fluorescence spectrometer. The excitation wavelength was set to 380 nm, the slit width was set to Ex: 1.03 nm; Em: 1.00 nm, and the test speed was set to fast. Please refer to the test results. Figure 2 .

[0067] From the results, it can be seen that the materials doped with Cu2+ all show stronger PL values ​​than those of the undoped Cu2+ in Example 1. The PL wavelengths of the materials doped with Cu2+ first blue-shift and then red-shift in sequence, and the fluorescence emission intensity of Example 3 is the highest.

[0068] 2. X-ray powder diffraction (XRD) test: The luminescent particles finally obtained in step 5 of Examples 1 to 7 were dried in vacuum at 50°C for 24 hours to obtain dry powder. The test was conducted using a Panalytical X'PERT Pro instrument, and the crystal structure of the perovskite was characterized under the parameters of 40 kV, 35 mA copper target Ka radiation, 2θ = 5 to 60°. The spectrum was processed using Jade 9 software, and the corresponding standard card was selected. The XRD pattern of the test was as follows: Figure 3 shown.

[0069] The results show that doping with Cu2+ does not change the crystal structure of Cs3Bi2Br9 perovskite, but due to the Cu2+ ion radius Smaller than the Bi3+ ion radius When Cu2+ is doped into the Cs3Bi2Br9 perovskite lattice, it causes the lattice to shrink, thereby changing the material's energy band structure, especially affecting the energy difference between the valence band and the conduction band, i.e., the band gap. The change in the band gap directly affects the optical and electrical properties of the material: as the band gap decreases, the material is more likely to absorb visible or infrared light, thereby improving its photoelectric conversion efficiency or photocatalytic performance.

[0070] 3. Fluorescence quantum yield (PLQY) test: 2 mL of liquid material was placed in a quartz cuvette and tested at room temperature using an FLS980 fluorescence spectrometer (Edinburgh Instruments, UK). During the test, a specific 375 nm excitation light source was selected and the lifetime was obtained using software processing; then the emission quantum yield was obtained by combining the integrating sphere in the fluorometer, and finally the quantum yield was calculated using the Edinburgh L980 software package. The results are as follows: Figure 4 shown.

[0071] It can be seen from the results that the PLQY of Example 3 is increased by 102% compared with Example 1, which indicates that the fluorescence performance of Cs3Bi2Br9:Cu2+ is effectively improved after doping.

[0072] 4. Water stability test: Take 2 ml of the colloidal solution prepared in step 5, add 0.0 ml, 0.2 ml, 0.4 ml, 0.6 ml, 0.8 ml, 1.0 ml, 1.5 ml and 2.0 ml of ultrapure water respectively, and conduct a water gradient stability experiment. In order to explore the stability of bismuth-based perovskite nanocrystals after Cu2+ doping, the optimal doping ratio and undoped perovskite are dispersed in 50% water respectively, and the relative fluorescence intensity of the two at different times is tested to obtain the fluorescence change curve. The test results are shown in Figure 2. Figure 5 and Figure 6 shown.

[0073] The results show that Cu doped 2+ After adding water, the fluorescence intensity of the Cs3Bi2Br9 quantum dots showed a trend of first increasing and then decreasing. When 0.8 ml of water was added, the fluorescence intensity of the quantum dots was maximized, which was 120% of the fluorescence intensity of Example 1. The perovskites of Example 3 and Example 1 were dispersed in 50% water respectively, and the fluorescence intensity showed a trend of first increasing and then decreasing over time. After standing for 18 hours, the quantum dots doped with Example 3 still maintained a relative fluorescence enhancement of 106%, and maintained a stronger relative fluorescence intensity than Example 1.

[0074] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A copper-doped bismuth-based perovskite luminescent material, characterized in that: The structural formula is Cs3Bi2Br9:Cu 2+ .

2. The copper-doped bismuth-based perovskite luminescent material according to claim 1, characterized in that: The raw materials include a precursor solution, a CuBr2 ethanol solution and an oleic acid-ethanol solution. The raw materials of the precursor solution include CsBr, BiBr3, dimethyl sulfoxide and n-octylamine, and the ratio of CsBr:BiBr3:dimethyl sulfoxide:n-octylamine is 0.3-0.5 mmol:0.2-3.3 mmol:5.8-6.3 ml:60-70 μl; the molar ratio of CsBr / BiBr3 is 1.3-1.6; The raw materials of the CuBr2 ethanol solution include anhydrous ethanol and CuBr2, wherein the anhydrous ethanol:CuBr2 is 2.3-2.6 ml:0.05-0.06 mmol; The oleic acid-ethanol solution comprises the following raw materials in parts by volume: 4.3-5 parts of anhydrous ethanol and 0.35-0.6 parts of oleic acid; The ratio of the sum of the volumes of the CuBr2 ethanol solution and the oleic acid-ethanol solution to the volume of the precursor solution is 10:

1.

3. A method for preparing a copper-doped bismuth-based perovskite luminescent material, characterized in that: The following steps are involved: Step 1, CsBr, BiBr3, dimethyl sulfoxide, and n-octylamine are mixed until the particles in the solution are completely dissolved to obtain a precursor solution; Step 2, mixing CuBr2 with anhydrous ethanol and stirring until the particles in the solution are completely dissolved to obtain a CuBr2 ethanol solution; Step 3, mixing anhydrous ethanol and oleic acid to obtain an oleic acid-ethanol solution; Step 4, mixing the CuBr2 ethanol solution with the oleic acid-ethanol solution, and then injecting the precursor solution at 50-90° C. to obtain a quantum dot solution; Step 5, separating the supernatant of the quantum dot solution to obtain a colloidal solution.

4. The method for preparing a copper-doped bismuth-based perovskite luminescent material according to claim 3, characterized in that: The stirring temperature in step 1 is room temperature.

5. The method for preparing a copper-doped bismuth-based perovskite luminescent material according to claim 3, characterized in that: At least one of step 1 and step 2 is performed by stirring or ultrasonic dissolution during mixing.

6. The method for preparing a copper-doped bismuth-based perovskite luminescent material according to claim 3, characterized in that: Step 4: Mixing was performed at 85°C.

7. The method for preparing a copper-doped bismuth-based perovskite luminescent material according to claim 6, characterized in that: The stirring time of step 4 is 10 min.

8. The method for preparing a copper-doped bismuth-based perovskite luminescent material according to claim 3, characterized in that: In step 5, separation is performed by centrifugation at a speed of 5000 to 8000 rpm for 5 to 10 minutes to separate the clear liquid and obtain a liquid material.

9. The method for preparing a copper-doped bismuth-based perovskite luminescent material according to claim 8, characterized in that: Step 5: The liquid material is separated again by centrifugation, and the centrifugal speed is greater than or equal to 10000 rpm, the centrifugal time is greater than or equal to 10 min, and the precipitate is separated to obtain a solid material.

Citation Information

Patent Citations

  • Method for preparing perovskite nanocrystals by using oleic acid ligand as solvent and ultrasonic-assisted method

    CN114702068A

  • A perovskite single crystal-based hand-held x-ray detector and its method thereof

    IN202211051569A